Safe abortion? Ethical aspects of the use of the abortion pill RU-486 - Kobyliński, Andrzej (Studia Ecologiae et Bioethicae, 2017)
The article focuses on the ethical aspects of chemical abortion, also known as pharmaceutical or medical abortion. Chemical abortion is typically done using two drugs. The first is mifepristone, also known as RU-486, and the second is misoprostol. The drugs are taken orally over three days, although the abortion itself may take much longer to complete. Mifepristone is an antiprogestin: it works by blocking the pregnancy hormone progesterone. Progesterone is „pro-gestation”, as the name suggests, and makes the nutrients in the uterine lining available to the newly-conceived fetus as it arrives from the fallopian tube. A chemical abortion causes a serious reaction in a woman’s body in order to cause it to interrupt and expel the pregnancy. The global phenomenon of medical abortion opens today a new stage of the public dispute about the beginning of human life and the recognition of the human embryo as the human being from the very moment of conception.